التحول الرقمي في القطاع المصرفي(التجربة السعودية أنموذجا) - لنصاري، امباركة; مسعي محمد، سليمة; رقاني، لالة فاطمة (University Of Eloued جامعة الوادي, 2024)
هدفت الدراسة إلى التعرف على واقع التحول الرقمي في القطاع المصرفي وتحديدا في القطاع البنكي بالمملكة العربية السعودية، وقد تم تسليط الضوء فيها على مفهوم التحول الرقمي وإبراز دوره وأهميته في المؤسسات المالية والمصارف بصفة خاصة عن طريق تقديم خدمات ذات أداء متميز في وقت أقل وبتكلفة منخفضة بالإضافة إلى تحقيق الربحية وزيادة المنافسة. وذلك من خلال التطرق إلى تجربة السعودية في اعتماد التحول الرقمي في البنوك. وقد توصلت الدراسة إلى مجموعة من النتائج نذكر منها: معرفة الدور الكبير للتحول الرقمي كآلية لتحسين أداء البنوك، التحول الرقمي أحد المرتكزات الأساسية لنمو ونجاح المؤسسات المصرفية، يساعد توظيف التقنيات الرقمية الحديثة في عمل البنوك على تطوير المنتجات والخدمات المالية الرقمية، ويساهم في تعزيز أدائها؛ ويسمح للبنوك بمواكبة التطورات الهائلة في مجال التكنولوجيات المالية الحديثة. Abstract: The study aimed to identify the reality of digital transformation in the banking sector, specifically in the banking sector in the Kingdom of Saudi Arabia. The study highlighted the concept of digital transformation and highlighted its role and importance in financial institutions and banks in particular by providing services with distinguished performance in less time and at a low cost, in addition to achieving profitability and increasing competition. This was done by addressing the Saudi experience in adopting digital transformation in banks. The study reached a set of results, including: Knowing the major role of digital transformation as a mechanism to improve the performance of banks, digital transformation is one of the basic pillars of the growth and success of banking institutions, employing modern digital technologies in the work of banks helps to develop digital financial products and services, and contributes to enhancing their performance; and allows banks to keep pace with the tremendous developments in the field of modern financial technologies.
Digital Transformation in the Banking Sector (The Saudi Experience as a Model)
مداخلة
Keywords: تحول رقمي; قطاع مصرفي; المملكة العربية السعودية; Digital transformation; banking sector; Kingdom of Saudi Arabia